System facilitators and barriers to discussing older driver safety in primary care settings - Betz, Marian E. (Inj Prev, 2015)
BACKGROUND: Primary care physicians play a leading role in counseling older drivers, but discussions often do not occur until safety concerns arise. Prior work suggests that routine questioning about driving might facilitate these difficult conversations. OBJECTIVE: To explore system-level factors affecting driving discussions in primary care settings, in order to inform the design and implementation of a program supporting routine conversations. METHODS: This qualitative descriptive study used iterative interviews with providers (physicians, nurses, medical assistants, social workers, and administrative staff) working at two clinics (one geriatric, one general internal medicine) at a tertiary-care teaching hospital. General inductive techniques in transcript analysis were used to identify stakeholder-perceived system-level barriers and facilitators to routine conversations with older drivers. RESULTS: From fifteen interviews, four themes emerged: (1) complexity of defined provider roles within primary care setting (which can both support team work and hamper efficiency); (2) inadequate resources to support providers (including clinical prompts, local guides, and access to social workers and driving specialists); (3) gaps in education of providers and patients about discussing driving; and (4) suggested models to enhance provider conversations with older drivers (including following successful examples and using defined pathways integrated into the electronic medical record). A fifth theme was that participants characterized their experiences in terms of current and ideal states. CONCLUSIONS: Physicians have been tasked with assessing older driver safety and guiding older patients through the process of “driving retirement.” Attention to system-level factors such as provider roles, resources, and training can support them in this process.